ANALYSIS OF BRAND STRATEGIES AND BRAND ADVOCATES STRATEGIES IN BASMALAH MART SIDOGIRI - Mochamad Ainul Yaqin; Hamidah Tusiffah (University of Darussalam Gontor, 2020)
The retail business competition in East Java is currently very competitive. The actors are competing to win the hearts of consumers by creating a company that has its own characteristics. One way to create a distinctive company characteristic is brand strategy, because at this time the product strategy will be easily demonstrated by competitors. By contrast, the brand strategy will strengthen the image of the product to the costumer’s choices. Several cases that often occur in consumers are consumers manifest themselves in the form of product purchases, with changes in these properties, consumers who previously only bought because of need, at present satisfied consumers will buy the preferred brand even though the needs have been. In the formation of consumer traits as it is today, it is not wrong if the company establishes brand advocates, with brand advocates that companies can form consumers who recommend, love, and even defend companies from detractors and attackers. Basmalah mart is a retail store owned by the Sidogiri Islamic Boarding School which no person or group has criticized and attacked Basmalah mart. The purpose of this research is to find out how Basmalah mart applies brand strategy and brand advocates. This study uses descriptive qualitative methods. Data retrieval is conducted by using observation, interview, documentation and triangulation data. From this study, it can be concluded that Basmalah mart has succeeded in carrying out a brand strategy and brand advocates. The implementation and practice carried out by Basmalah mart has been done well, because Basmalah mart does and has products that are in accordance with all indications of the proprietary brand strategy, namely: new brand strategies, multi-brand strategies, brand extension strategies, brand line expansion strategies. The application of the Basmalah mart in carrying out and forming brand advocates is by creating unique products, providing exellent services, providing benefits to consumers, forming consumer trust, social responsibility. From these results, it is expected that the managerial Basmalah mart can maximize its strength and optimize its performance. In addition the reseacher suggest tje menegement to update the SOP in creating new products immediately.